2005
DOI: 10.3168/jds.s0022-0302(05)72964-7
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Enteric Methane Emissions and Animal Performance of Late-Lactation Dairy Cows Through Concentrate Supplementation at Pasture

Abstract: The objective of this study was to determine the potential of increased fiber-based concentrates to reduce methane (CH(4)) production in relation to milk yield from late-lactation dairy cows. The effect of 2 levels of concentrate supplementation (0.87 vs. 5.24 kg on a dry matter basis) on herbage voluntary intake, total dry matter intake, milk yield, milk composition, and CH(4) production were determined by way of a randomized block designed grazing trial using lactating Holstein-Friesian cows (231 +/- 44 d in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
47
6
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 19 publications
(34 reference statements)
13
47
6
6
Order By: Relevance
“…This was due to the proteinenergetic mineralised salt used because it acts as an amender in the feed conversion rate and reduces the time to achieve the fattening weight (510 days). These results were consistent with those of other studies demonstrating that higher quality forage, the use of concentrated, essential oils or increased growth rates reduced methane and nitrous oxide emitted from manure, both of which are key emission gases (Benchaar and Greathead, 2011;Casey and Holden, 2006;Lovett et al, 2005).…”
Section: Resultssupporting
confidence: 92%
“…This was due to the proteinenergetic mineralised salt used because it acts as an amender in the feed conversion rate and reduces the time to achieve the fattening weight (510 days). These results were consistent with those of other studies demonstrating that higher quality forage, the use of concentrated, essential oils or increased growth rates reduced methane and nitrous oxide emitted from manure, both of which are key emission gases (Benchaar and Greathead, 2011;Casey and Holden, 2006;Lovett et al, 2005).…”
Section: Resultssupporting
confidence: 92%
“…Substitution of beet pulp by barley in a high concentrate diet (70%) fed to dairy cows reduced CH 4 emissions by 34% (Beever et al, 1989). Lovett et al (2005) reported that this was not the case when fresh forages were the main ingredients of the basal diet. Beauchemin and McGinn (2005) measured CH 4 emissions from feedlot cattle fed backgrounding and finishing diets containing maize (slowly degradable starch) or barley grain (rapidly degradable starch).…”
Section: Mitigation Through Feedingmentioning
confidence: 99%
“…Like CO 2 and nitrous oxide (N 2 O), CH 4 has the capacity to raise earth's temperature through the absorption of long-wave radiation -E-mail: mizeck.chagunda@sruc.ac.uk (Lovett et al, 2005). The Intergovernmental Panel for Climate Change (IPCC) has reported sharp increases in concentrations of GHG mainly because of human activities (IPCC, 2007).…”
Section: Introductionmentioning
confidence: 99%